Protecting Cross-Border Workers Within the EU: A Comparative Study Between Italy and the Netherlands - Russo, Marianna (Central European Academy Law Review, 2025)
This paper aims to identify the most insidious challenges and the most effective remedies to guarantee the principle of equal treatment and non-discrimination on grounds of nationality. It does so by analysing regulatory frameworks, case law and data on cross-border workers from a comparative perspective, with special focus on Italy and the Netherlands.